An Interesting Pathological Diagnosis – Adenoid Cystic Carcinoma in an Adolescent Girl - Ingle, Sachin B (Breast Cancer (Auckl), 2015)
Adenoid cystic carcinomas (ACCs) constitute 0.1–1 % of all malignant breast tumors. They have better prognosis than other breast malignancies. To date, there have been about 933 cases reported as per English literature. To the best of our knowledge, this case may be the second well-documented case of ACC of breast at younger age.